Stegano-image as a digital signature to improve security authentication system in mobile computing - Mantoro, Teddy; Permadi, Didit Dwi; Abubakar, Adamu (IEEE, 2016)
Authentication of any system means providing a security to that system. Securing confidential information on the mobile platforms has been becoming a typical issue for the specialists. One of the authentication techniques is a textual password based. This type of textual password commonly follows an encryption algorithm to provide security. This techniques has some limitations and drawbacks. When users choose meaningful words from dictionaries, by using brute force attacks, it makes textual passwords vulnerable to dictionary and easy to break. To overcome the drawbacks, a new authenticate technique is proposed in this paper in order to provide for more security authentication system. In this paper the textual password will be hidden in an image using steganography technique. All data and critical information like passwords are stored in encrypted manner used image as carrier so it's difficult for brute force attack to crack it. Steganography is used to hide secret information onside some carrier. The most basic and important image steganography technique is Least Significant Bit (LSB) embedding technique. In this technique, data can be hidden in the least significant bits of the cover image and the human eye would be unable to notice the hidden image in the cover file. LSB steganography is combined with AES cryptography to hide textual password, in order to provide high level security on authentication system that run under Android